Lipstick Clapsticks: A yarn and a Kiki with an Aboriginal drag queen. (December 2016) - Farrell, Andrew
With Aboriginal drag queens you never just "spin a yarn"—you have a Kiki. As depicted in the film Paris Is Burning (Livingston, 2005), having a "Kiki" means to discuss, chatter, gossip, and have a good time with your "good Judys", your girlfriends. It is a term created by transgender and Queer people of colour that I respectfully adopt in sharing my stories and experiences as a Queer-identified Aboriginal Australian who practices and enjoys the multifaceted art of drag transformation and performance. In the spirit of a Kiki, this article will give you an insight into my world as a gender-defying Queer Aboriginal drag queen.